Delivering Successful Projects with TSP(SM) and Six Sigma - Jain, Mukesh (CRC Press, 2009)
Delivering successful projects means the ability to produce high quality software within budget and on time—consistently, but when one mentions quality to software engineers or project managers, they talk about how impossible it is to eliminate defects from software. This assumption is passed on and on until it becomes accepted wisdom, with the power of a self-fulfilling prophecy. And when a project fails to arrive on time or up to standards, team members will turn on each other. The project got delayed because the engineers did a poor job in development or too much was promised upfront for this short of a timeline.